2017
DOI: 10.21037/cdt.2017.09.15
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed thrombolysis of deep vein thrombosis: literature review and practice considerations

Abstract: Deep vein thrombosis (DVT) is a major health problem worldwide. The risk of pulmonary embolism following DVT is well established, but the long-term vascular sequelae of DVT are often underappreciated, costly to manage, and can have extremely detrimental effects on quality of life. Treatment of DVT classically involves oral anticoagulation, which reduces the risk of pulmonary embolism but does not remove the clot. Anticoagulation therefore does little to prevent the venous damage and scarring that occurs follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 59 publications
1
87
0
2
Order By: Relevance
“…Perrier et al 16 also concluded that CDT should be performed for the patients≤50 years old with extensive proximal DVT with a high risk of developing a severe PTS and low bleeding risk in terms of cost-effectivity 16 . A recently published review also supported the idea that CDT is a costeffective method, particularly for patients with long life expectancy 17 . In present study, we demonstrated that UACDT was an effective method for acute iliofemoral DVT, particularly for patients with a patent popliteal vein.…”
Section: Discussionmentioning
confidence: 80%
“…Perrier et al 16 also concluded that CDT should be performed for the patients≤50 years old with extensive proximal DVT with a high risk of developing a severe PTS and low bleeding risk in terms of cost-effectivity 16 . A recently published review also supported the idea that CDT is a costeffective method, particularly for patients with long life expectancy 17 . In present study, we demonstrated that UACDT was an effective method for acute iliofemoral DVT, particularly for patients with a patent popliteal vein.…”
Section: Discussionmentioning
confidence: 80%
“…Serial hematocrit levels and coagulation function assay should be mandatory, 21,22 and it was performed daily in the present study. The frequency of testing was less than that accepting anticoagulation therapy with unfractionated heparin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal anti-factor Xa level was unknown during CDT. 21,23 The assay was not available at that time in our center. Further studies evaluating optima anti-factor Xa level during CDT should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…9 IVC filtration is associated with an 18.6% incidence of vena cava thrombosis, resulting in a 1% rate of IVC total occlusion. 10 Though catheter-directed thrombolysis has been shown to be effective in the treatment of proximal deep vein thrombosis, 11 there are no reports in the literature for its use in POVT. Surgical options are reserved for those patients who fail medical management or develop pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%